THE POSSIBILITY OF RELIGIOUS EXPERIENCE IN ISLAMIC THEOLOGY - Tajdin, Mustapha (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2021)
In the present article, the author explores the possibility of religious experience from the perspective of Islamic theology. The article seeks to unearth the seeds of religious subjectivism in Islam based on a theoretical framework grounded in the modern concept of religious experience. The practical aim of this undertaking is to escape the pitfalls of religious traditionalism on the one hand, and to repudiate the claim that Islam is ill disposed towards spirituality on the other hand. At the core of any religion, there is the individual’s encounter with the Divine. The emphasis on the personal spiritual experience would help Humanist and Universalist discourses on religion to lay the foundations for fruitful interfaith interactions, and reformulate theological systems, mainly the Islamic one, in order to respond positively to the challenges of globalisation and the threats of both extremism and exclusivism.